The impact of green supply chain practices on suitainable performance - Chong, Bi Chian; Abdullah, Rohani (2012)
With increases awareness of public’s to the environmental problem and the requirement meet the term of environmental policy green supply chain management becoming important to the manufacturing.Green supply chain practices can contribute improving manufacturer’s performance from environmental point, economic point and social point.The purpose of this paper is to explore the relationship among the green supply chain practices on the sustainable performance.This study will also identify the most important green supply chain practice.